TOLERANSI DAN INTOLERANSI DALAM DAKWAH - Luweni Wabisah; Bobby Rachman Santoso (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2021)
Abstract Tolerance in religious practices in Indonesia is an important component in realizing a peaceful society. However, in this modern era, there are still many cases of religious practices that misuse the meaning of tolerance for the benefit of the organization. Da'wah activities that always apply the principle of tolerance can attract mad'u interest in Islam, while intolerant activities carried out by mass organizations increasingly isolate da'wah activities from the public's attention. Of course, the term dakwah tolerance for various Islamic mass organizations in Indonesia is very diverse. For GP Ansor Ngantru, dakwah tolerance is the group's point of view not to blame each other on different groups in understanding fiqh or mahzab. Meanwhile, intolerance in da'wah is an anarchist act with an expression of hatred in diversity. For him, Islamic organizations in Indonesia must instill the principle of tolerance in preaching and abandon all actions that lead to radicalism and misery and loss of the people. Keyword: Da’wah, Tolerance, Intolerance